Efficacy and toxicity of Tanacetum vulgare and Rosmarinus officinalis essential oils novel biocontrol agents for sustainable management of Phthorimaea operculella, the potato moth - Fatima Mahboub (18024291) (2025)
Phthorimaea operculella, a major pest of potato crops, causes significant yield losses, prompting farmers to rely on harmful pesticides. This study evaluates the insecticidal activity of essential oils from Tanacetum vulgare and Rosmarinus officinalis as sustainable alternatives. Chemical analysis revealed that Tanacetum vulgare oil is primarily composed of o-Phenylanisole (25.41%), β-pinene (20.91%), and comphor (18.35%), while Rosmarinus officinalis contains Camphor (18.58%) and camphene (8.78%). Toxicity assays showed that Tanacetum vulgare oil exhibited an LC50 range from 1.277 to 6.628 µL/L, with an LC99 from 3.22 to 3482.24 µL/L. For Rosmarinus officinalis, LC50 ranged from 1.999 to 10.426 µL/L, with LC99 exceeding 100,000 µL/L. Both oils demonstrated significant toxicity to adult P. operculella, supporting their potential as eco-friendly pesticide alternatives.